An interdisciplinary theory-based ESL curriculum to teach English as a second language - Fuentes, Brenda; Soto Mas, Francisco; Mein, Erika; Jacobson, Holly E. (Colombian Applied Linguistics Journal, 2011)
Among Hispanic immigrants in the United States (US), learning English is considered necessary for economic and social achievement. As a consequence, there is a high demand for English as a Second Language (ESL) classes. Despite the recognized benefits of ESL programs, both at the individual and social levels, more research is needed to identify education strategies that effectively promote all aspects of learning English as a second language. This article describes an ESL curriculum that incorporates a theory-based pedagogical approach specifically designed for immigrant Hispanic adults on the US-Mexico border region. The article also describes the implementation of the curriculum as well as the results of the evaluation, which was conducted using both quantitative and qualitative methods. Quantitative results indicate that the participants significantly improved their English proficiency (L2). Qualitative results suggest that participants were positively impacted by both the content and pedagogical approaches used by the curriculum. Their experience with the ESL class was positive in general. It can be concluded that the curriculum achieved its objective. This approach could serve as a model for second language teaching for adults.